Wilson's Disease Caused by Previously Undescribed Homozygous Nucleotide Variant of the ATP7B Gene: Clinical Cases - Denis K. Chernevskiy; Alla E. Lavrova; Ekaterina Yu. Konovalova; Elena Yu. Borisova; Natalia A. Doroshchuk; Olga S. Groznova ("Paediatrician" Publishers LLC, 2024)
Wilson's disease is severe autosomal recessive disease manifested primarily by hepatic, neurological, and psychiatric disorders due to excessive copper deposition in organs and tissues. Clinical case description. The variant with uncertain clinical value of the ATP7B gene, c.2111C>T (p.T704I, chr13:52534294G>A (HG19)), was described in the family where parents are cousins. The eldest daughter out of four children died at the age of 11 due to liver cirrhosis. Wilson's disease was genetically confirmed in two children (clinically - abdominal form). The younger son was diagnosed heterozygous state of the disease (without any clinical manifestations). The revealed variant of the ATP7B gene was previously identified in 3 more patients with Wilson's disease, however, in a compound heterozygous state with known pathogenic genetic variant. Conclusion. c.2111C>T (p.T704I) variant of the ATP7B gene can be considered as probably pathogenic. Further research is required to evaluate its functional significance in Wilson's disease pathogenesis.